Dynamics of a Higher Education Institutional Partnership in a Finnish Nepalese Capacity Building Project - Do-Salenius, Phuong (2019)
North South partnerships in higher education are widely implemented through joint capacity building projects. An authentic partnership needs beneficiary engagement in both planning and executing development strategies to achieve the desired outcomes. This thesis examines the dynamics of an institutional partnership between Finnish and Nepalese higher education institutions in a capacity building project with a focus on a training program organized in Finland. Utilizing data from a participant evaluation questionnaire and semi- structured interviews, the study seeks to explore how the institutional partnership contributes to ensuring the goal of reaching the needs of the science, maths and social sciences teachers of Nepalese higher education institution who desire to apply open and distant learning model into their local educational setting. The qualitative research embraces the voices of the project stakeholders from both institutions and from different standpoints including administrators, coordinators and teacher participants. The road to an authentic partnership addressing the beneficiaries’ needs requires essential practices of mutuality, respect, trust, and transparency with a necessity of adequate time and effort in planning phase, open dialogue between the two partners, and attempts to prevail over the divergence in working cultures. The findings from this study makes a significant contribution to the project itself through reflective viewpoints and constructive recommendations from the teacher participants and the project staff, and propose implications for further research on institutional partnership in a similar context.